Analisis Keterlambatan Pengajuan Klaim Obat Kronis BPJS Kesehatan di Rumah Sakit BaliMed Karangasem - Wijaya, I Nyoman Satria (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2019)
The BPJS Health payment scheme to hospitals uses the INACBG and non INACBG payment schemes. One non-INACBG payment scheme is used for chronic drug services. BaliMed Hospital Karangasem as one of the BPJS Health partners also serves chronic medicine services to be paid by BPJS Kesehatan with a non-INACBG payment scheme. In September 2018, the hospital has not collected chronic drug claims that have been served despite the amount in the previous year the chronic drug claim bill did not exceed 10% of the total claim for one year but this must still be billed to reduce the burden of hospital financing. This research is a qualitative research by brainstorming with related units to be described as a fishbone diagram to find the root cause. The results of the root cause analysis are the absence of the authority given by the director to the team or person to be responsible for the claim submission process. The process involving many of these units requires special attention and regulation so that with the appointment of directors the technical flow and design of information systems that facilitate the process of preparing chronic drug claims can be more effectively and efficiently designed.